Sympathetic Interfaces: Using a Plush Toy to Direct Synthetic Characters - Johnson, Michael Patrick; Wilson, Andy; Blumberg, Bruce; Kline, Christopher; Bobick, Aaron (CHI '99 Proceedings of the SIGCHI conference on Human Factors in Computing Systems, 1999)
We introduce the concept of a sympathetic interface for controlling an animated synthetic character in a 3D virtual environment. A plush doll embedded with wireless sensors is used to manipulate the virtual character in an iconic and intentional manner. The interface extends from the novel physical input device through interpretation of sensor data to the behavioral “brain” of the virtual character. We discuss the design of the interface and focus on its latest instantiation in the Swamped! exhibit at SIGGRAPH ‘98. We also present what we learned from hundreds of casual users, who ranged from young children to adults.